2014
DOI: 10.1177/0895904814550069
|View full text |Cite
|
Sign up to set email alerts
|

Science Standards, Science Achievement, and Attitudes About Evolution

Abstract: This article explores the relationships between (a) the quality of state science standards and student science achievement, (b) the public’s belief in teaching evolution and the quality of state standards, and (c) the public’s belief in teaching evolution and student science achievement. Using multiple measures, we find no evidence of a relationship between the quality of a state’s science standards and student science achievement. We also examine the relationship between state-level beliefs about evolution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Additional measures of broad student knowledge-ACT Math score and cumulative college GPA at the start of term-were also included in our investigation. While geographical location and context may impact students' evolution acceptance (Berkman and Plutzer 2011;Belin and Kisida 2014), we also did not address this as a variable in our study. A final limitation of our study is that we did not include a measure of religiosity, a variable which has been repeatedly reported to have a significant association with evolution acceptance (Smith 2010;Rissler et al 2014;Dunk et al 2017).…”
Section: Measures Of Student Performance and Evolution Acceptancementioning
confidence: 97%
“…Additional measures of broad student knowledge-ACT Math score and cumulative college GPA at the start of term-were also included in our investigation. While geographical location and context may impact students' evolution acceptance (Berkman and Plutzer 2011;Belin and Kisida 2014), we also did not address this as a variable in our study. A final limitation of our study is that we did not include a measure of religiosity, a variable which has been repeatedly reported to have a significant association with evolution acceptance (Smith 2010;Rissler et al 2014;Dunk et al 2017).…”
Section: Measures Of Student Performance and Evolution Acceptancementioning
confidence: 97%
“…Smith () outlines utilitarian, economic, democratic, cultural, and moral reasons to include evolution in science education, and Heddy and Nadelson () found a strong positive correlation between evolution acceptance and science literacy as well as GDP (Gross Domestic Product) per capita across 35 countries—though not the US, which has a lower level of public acceptance of evolution than expected for its GDP per capita. Within the US, evolution acceptance and GDP per capita are strongly correlated across states (Heddy and Nadelson, ) and a recent study demonstrated a clear and consistent relationship between a state's public acceptance of evolution and the levels of science achievement of students in that state (Belin and Kisida, ). It is argued that not accepting evolution limits peoples’ ability to make informed decisions about a wide range of phenomena, many of which have personal ramifications for their health (vaccines, medicine, biotechnology, and genomics) as well as the health of the planet (agriculture, conservation, biodiversity, and climate change) (Mead and Branch, ; Evans et al, ; Southerland and Nadelson, ; Brem and Sinatra, ; Nadelson and Hardy, ), because the modern theory of evolution undergirds other areas of science research ranging from anatomy to ecology to genetics (Hermann, ).…”
Section: Discussionmentioning
confidence: 98%